Assessing thermal adaptation of a global sample of Aspergillus fumigatus: Implications for climate change effects - Greg Korfanty; Erin Heifetz; Jianping Xu (Frontiers Media S.A., 2023)
Aspergillus fumigatus is a common environmental mold and a major cause of opportunistic infections in humans. It's distributed among many ecological niches across the globe. A major virulence factor of A. fumigatus is its ability to grow at high temperature. However, at present, little is known about variations among strains in their growth at different temperatures and how their geographic origins may impact such variations. In this study, we analyzed 89 strains from 12 countries (Cameroon, Canada, China, Costa Rica, France, India, Iceland, Ireland, New Zealand, Peru, Saudi Arabia, and USA) representing diverse geographic locations and temperature environments. Each strain was grown at four temperatures and genotyped at nine microsatellite loci. Our analyses revealed a range of growth profiles, with significant variations among strains within individual geographic populations in their growths across the temperatures. No statistically significant association was observed between strain genotypes and their thermal growth profiles. Similarly geographic separation contributed little to differences in thermal adaptations among strains and populations. The combined analyses among genotypes and growth rates at different temperatures in the global sample suggest that most natural populations of A. fumigatus are capable of rapid adaptation to temperature changes. We discuss the implications of our results to the evolution and epidemiology of A. fumigatus under increasing climate change.